Glucosamine effects on platelet aggregation of type 2 diabetes mellitus patients: in vitro assays: GlcN in platelet aggregation in T2D - Itandehui Belem, Gallegos-Velasco; Miguel Ángel, Pérez-Acevedo; Berenice, Fernández-Rojas; Pedro Antonio, Hernández-Cruz; Jesús, Hernández-Juárez (Cellular and Molecular Biology, 2023)
Hyperglycemia, insulin resistance, and endothelium dysfunction are related to platelet hyperactivity in type 2 diabetes mellitus (T2D) patients. Glucosamine (GlcN) has inhibitory effects on platelets of animals and healthy donors, but this role in platelets from T2D patients is unknown. The aim of this study was to evaluate the GlcN in vitro effects on platelet aggregation in T2D patients and healthy donors. Donors´ and T2D patients' samples were analyzed through flow cytometry, Western blot, and platelet aggregometry. Platelet aggregation was induced using ADP and thrombin, with or without GlcN, N-Acetyl-glucosamine, galactose, or fucose. GlcN inhibited ADP and thrombin-induced platelet aggregation, while the other carbohydrates did not. GlcN suppressed the second wave of ADP-induced platelet aggregation. No differences in the percent of inhibition of ADP-induced platelet aggregation by GlcN were found between donors and T2D patients, but this effect was significantly higher in healthy donors using thrombin as an agonist. In addition, GlcN increased protein O-GlcNAcylation (O-GlcNAc) in the platelets from T2D patients but not in healthy donors. In conclusion, GlcN inhibited the platelet aggregation induced by ADP and thrombin for both study groups and increased O-GlcNAc in platelets from T2D patients. Further studies are required to evaluate the possible use of GlcN as an antiplatelet agent.